2020
DOI: 10.1038/s41598-020-57985-w
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic ILC2 activity is regulated by liver inflammation-induced cytokines and effector CD4+ T cells

Abstract: In the present study, we investigated the phenotype and plasticity of hepatic ILC2 in response to liver inflammation-induced cytokines and effector CD4 + T cells in order to identify mechanisms of ILC2 regulation in liver disease. Material and Methods Mice. C57BL/6 mice and OT-II mice were bred in the University Medical Center Hamburg-Eppendorf animal facility (Hamburg, Germany). Mouse experiments were conducted according to the German animal protection law and approved by the institutional review board (Behör… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…Huang et al described a population of ST2 -KLRG1 hi inflammatory ILC2s that arise from gut-resident ILC2s following IL-25 stimulation or helminth infection; these inflammatory ILC2s enter the bloodstream and circulate to the lung where they regenerate the pool of "natural ILC2s". 50 While systemic treatment with IL-33 has been shown to expand KLRG1 hi ILC2s in mouse mesenteric lymph nodes or liver, 19,52 it is currently unclear whether all described inflammatory KLRG1 hi ILC2s constitute a single population with a common origin, or whether different subsets arise in different organs and in response to different stimulations. Notably, inflammatory ILC2s described in this study differ from IL-25/helminth-induced inflammatory ILC2s by their high expression of the IL-33 receptor subunit ST-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al described a population of ST2 -KLRG1 hi inflammatory ILC2s that arise from gut-resident ILC2s following IL-25 stimulation or helminth infection; these inflammatory ILC2s enter the bloodstream and circulate to the lung where they regenerate the pool of "natural ILC2s". 50 While systemic treatment with IL-33 has been shown to expand KLRG1 hi ILC2s in mouse mesenteric lymph nodes or liver, 19,52 it is currently unclear whether all described inflammatory KLRG1 hi ILC2s constitute a single population with a common origin, or whether different subsets arise in different organs and in response to different stimulations. Notably, inflammatory ILC2s described in this study differ from IL-25/helminth-induced inflammatory ILC2s by their high expression of the IL-33 receptor subunit ST-2.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, other studies reported expansion of liver ILC2s following systemic administration or hepatic expression of IL-33. 52,56,57 Moreover, in a recent review, Martinez-Gonzalez et al indicated that they observed increased ILC2 numbers in the blood and liver a few weeks after activation, although they did not specify the type of activation. 58 In light of these findings, we propose that systemic administration of IL-33 induces a population of bloodcirculating ILC2s that preferentially expand in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the adipose tissue, ILC2s are also present in the liver. Hepatic ILC2s maintain a small naïve inactive phenotype in healthy liver but become highly activated by IL-33 in cases of hepatitis ( 39 ). In addition, IL-33-activated hepatic ILC2s seem to show resistance to both IFN-γ and plasticity induced by IL-12 ( 39 ).…”
Section: Ilc2s In Diabetic Active Tissuesmentioning
confidence: 99%
“…Hepatic ILC2s maintain a small naïve inactive phenotype in healthy liver but become highly activated by IL-33 in cases of hepatitis ( 39 ). In addition, IL-33-activated hepatic ILC2s seem to show resistance to both IFN-γ and plasticity induced by IL-12 ( 39 ). Hepatic ILC2s have been shown to be players in pathologic tissue remodeling and fibrosis ( 40 , 41 ).…”
Section: Ilc2s In Diabetic Active Tissuesmentioning
confidence: 99%
“…These include but are not limited to promotion of postnatal lung alveolarization (13,14), stimulating epithelial repair and extracellular matrix production to repair wounds (15)(16)(17)(18)(19), regulating muscle cell metabolism and the clearance of necrotic debris during muscular injury and exercise (9,20,21), and regulating energy metabolism and the differentiation of beige adipose tissue to increase caloric expenditure and generate heat (22)(23)(24)(25)(26). To date, components of this pathway have been implicated in homeostatic maintenance in the skin (18,19), muscles (9,20), intestines (27,28), nervous system (29,30), liver (8,31,32), biliary tract (15), lungs (16), kidney (11), adipose tissue (33), among others. Emergent roles in the initiation and amplification of type 2 immunity are being described for other innate immune cells, such as mast cells and basophils, which produce alarmins and potently secrete other cytokines in some contexts (34,35).…”
Section: Pathways Of Innate-driven Type 2 Immunitymentioning
confidence: 99%